Bibliometric Analysis of STEM Robotics in Physics Education: Global Trends (2008-2024) Based on Scopus Data - Windrawan, I Gede; Wibowo, Firmanul Catur; Sugihartono, Iwan (Universitas Lambung Mangkurat, 2024)
This study aims to analyze global trends in STEM-based robotic physics education through a bibliometric analysis conducted using data obtained from the Scopus database. STEM and robotics are increasingly gaining attention as effective approaches in physics education, aligning with the 21st-century demand for technical skills, creativity, and problem-solving abilities. This research utilizes R bibliometric software to identify publication patterns, researcher collaborations, and key trends in STEM-based robotic physics education from 2008 to 2024. The methods involved searching for articles using the keywords